Using Vis/NIR hyperspectral imaging and wavelength selection for accurate postharvest discrimination of similar loquat cultivars - Castillo-Gironés, Salvador; Munera, Sandra; Rodríguez, Alejandro; Aleixos, Nuria; Cubero, Sergio; López-Chulia, Marina; Martínez-Onandi, Nerea; Blasco, José (2024)
Similar fruit cultivars can be mixed in postharvest and sold as the same, whereas their quality might differ considerably. These differences in quality between cultivars can lead to rejection by consumers if the fruit does not meet their expectations. Thus, confusion must be avoided. Destructive methods to analyse composition are expensive and cannot be performed on all fruits. Alternatively, hyperspectral imaging is a non-destructive technology that has already been used to assess the internal quality of fruit. 'Algerie' is a traditional cultivar known for its sweet taste, while 'Xirlero' is a lower-quality new variety. Both varieties are harvested in the same period and have a similar external appearance, making them difficult to distinguish. This work aims to find a non-destructive way to distinguish between these two varieties, as the external appearance is similar, but the internal quality differs. 300 samples of 'Xirlero' loquat and 259 'Algerie' were used in the experiments. Samples were harvested weekly in a commercial orchard for five weeks to obtain several maturity levels.